2014
DOI: 10.1016/j.gep.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA processing machinery in the developing chick embryo

Abstract: Gene expression regulation during embryo development is under strict regulation to ensure proper gene expression in both time and space. The involvement of microRNAs (miRNA) in early vertebrate development is documented and inactivation of different proteins involved in miRNA synthesis results in severe malformations or even arrests vertebrate embryo development. However, there is very limited information on when and in what tissues the genes encoding these proteins are expressed. Herein, we report a detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Namely, miR-125a-5p is required for cyclic LFNG expression in the chick PSM 11 and miR-9 drives Hes1 oscillations in mouse neural progenitor cells 12 . Additionally, we previously showed that the genes encoding the enzymatic machinery for miRNA biogenesis are expressed in both the chick PSM and forelimb bud 13 , tissues where the EC is oscillating.…”
Section: Background and Summarymentioning
confidence: 99%
“…Namely, miR-125a-5p is required for cyclic LFNG expression in the chick PSM 11 and miR-9 drives Hes1 oscillations in mouse neural progenitor cells 12 . Additionally, we previously showed that the genes encoding the enzymatic machinery for miRNA biogenesis are expressed in both the chick PSM and forelimb bud 13 , tissues where the EC is oscillating.…”
Section: Background and Summarymentioning
confidence: 99%
“…Each set of lungs/probe was processed simultaneously and developed for the same amount of time, and then photographed with an Olympus U-LH100HG camera coupled to an Olympus SZX16 stereomicroscope. Antisense digoxigenin-labeled RNA probes for drosha, dgcr8, exportin-5 and dicer1 were produced as previously described (Carraco et al 2014). …”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…For example, Santarelli et al found that elevated miRNA levels occurred with a schizophreniaassociated increase in Dicer expression that facilitated pre-miRNA processing (Santarelli et al, 2011). For miRBGs in animals, relevant research also certified their profound effects on diverse cellular processes (Byon et al, 2014;Carraco et al, 2014;Li et al, 2014). Although we have little evidence in plants, research in model plants such as Arabidopsis thaliana has produced major advances in understanding the relationship between miRBGs and variations in phenotype.…”
Section: Introductionmentioning
confidence: 99%